Effects of time-restricted feeding and weight-loaded swimming test on androgen levels and androgen receptor expression in orchiectomized male Wistar rats - Liow, Chun Hung; Mohd Esa, Norhaizan; Yaacob, Azhar; Abu Saad, Hazizi (Elsevier, 2025)
Background & aims: Testosterone, vital for reproductive health and muscle development, declines with age, increasing susceptibility to conditions like diabetes, obesity and sarcopenia. Conventional hormone therapy carries risks, including elevated prostate-specific antigens and prostate cancer risk, prompting exploration of safer options like intermittent fasting (IF) and physical training (PT) which potentially boost androgen in certain cases. However, their combined impacts on testosterone remain underexplored. This study aimed to assess the individual and combined effects of IF and PT on androgen and androgen receptor (AR) levels. Methods: Forty male Wistar rats were divided into five groups (n = 8 each): negative control (NC) receiving food ad libitum without orchiectomized, positive control (PC) receiving daily testosterone enanthate injections, IF with 16/8 time-restricted feeding, PT with 1-h forced swimming sessions, and combined IF + PT. After 8 weeks, DHEA and testosterone levels, AR expression, gastrocnemius muscle histology, and body weight were assessed. Results: In comparison to the NC group (429.40 ± 26.86 g), body weight in the IF (348.90 ± 15.94 g, PT (391.40 ± 16.35 g), and IF + PT groups, (360.90 ± 29.90 g) was significantly lowered (p < 0.05) after 8 weeks of study. The muscle fiber cross-sectional area in the IF (2968 μm2; IQR 1995–4053 μm2), PT (2956 μm2; IQR 2089–4371 μm2), and IF + PT groups, (3389 μm2; IQR 2260–4596 μm2) was significantly greater than the NC group (2508 μm2; IQR 1800–3567 μm2. p < 0.05) after the study. DHEA levels significantly increased in the PT and IF + PT groups (375.01 ± 32.55 ng/μL and 420.00 ± 24.50 ng/μL, respectively) compared to the NC group (257.09 ± 67.79 ng/μL, p < 0.05). However, neither IF nor PT, alone or in combination, resulted in improvements in testosterone levels or AR expression in the gastrocnemius muscle. with testosterone levels remained unchanged. Conclusion: IF, PT, and IF + PT demonstrated potential effects on improving androgen levels, managing weight, and enhancing muscle growth, with IF + PT emerging as the most effective intervention. Despite these positive outcomes, the lack of impact on AR expression and testosterone levels suggests the need for further research to elucidate the underlying mechanisms and potential clinical applications for managing androgen deficiency through these interventions.